Baitul Maal learning organization in producing quality zakat accounting information - Marjulin Marjulin; Yusri Hazmi; Hilmi Hilmi; Teuku Zulkarnain; Busra Busra (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
This study aims to provide a basic understanding of the importance of organizational learning in producing quality zakat accounting information in Baitul Mal in Aceh. The methods used in this study are descriptive methods and explanatory research methods, and data will be collected by distributing questionnaires to zakat managers. who are members of the Baitul Mal institution. The data will be processed using a statistical tool, namely Partial Least Square (PLS) based on covariates. The results of this study prove that continuous organizational learning has an impact on the quality of information produced, this can be seen from the hypothesis test which shows that the organizational learning variable produces a number of 2.293 which is greater than the critical 1.65. Since the value of arithmetic is greater than critical, then at an error rate of 5% it is decided to reject Ho. So based on the test results, it can be concluded that organizational learning has a significant effect on the quality of zakat accounting information in Baitul Mal Aceh. So that the more frequent holding of training activities, seminars and symposia as well as opportunities to continue formal education for zakat managers will affect the quality of zakat management financial statements so that the reports produced contain accurate, timely, relevant and complete information, which can be useful in decision making.